2008
DOI: 10.1371/journal.pone.0003434
|View full text |Cite
|
Sign up to set email alerts
|

Foot-and-Mouth Disease Virus Persists in the Light Zone of Germinal Centres

Abstract: Foot-and-mouth disease virus (FMDV) is one of the most contagious viruses of animals and is recognised as the most important constraint to international trade in animals and animal products. Two fundamental problems remain to be understood before more effective control measures can be put in place. These problems are the FMDV “carrier state” and the short duration of immunity after vaccination which contrasts with prolonged immunity after natural infection. Here we show by laser capture microdissection in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 36 publications
6
78
2
2
Order By: Relevance
“…The signaling through CD40 is dependent on complement, specifically through C4b binding protein in the absence of the T-cell-derived CD40 ligand CD154 (9,26,48,60,65). We have shown previously with cattle that FMDV localizes to germinal centers as early as 3 to 4 days postchallenge (35), a process that may provide the signals required for T-I isotype class switching and an early FMDV-specific IgG response (26,47). The tumor necrosis factor family ligands BAFF and APRIL have also been shown to contribute to CD154-independent antibody isotype switching, germinal center maintenance, and T-I antibody responses (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signaling through CD40 is dependent on complement, specifically through C4b binding protein in the absence of the T-cell-derived CD40 ligand CD154 (9,26,48,60,65). We have shown previously with cattle that FMDV localizes to germinal centers as early as 3 to 4 days postchallenge (35), a process that may provide the signals required for T-I isotype class switching and an early FMDV-specific IgG response (26,47). The tumor necrosis factor family ligands BAFF and APRIL have also been shown to contribute to CD154-independent antibody isotype switching, germinal center maintenance, and T-I antibody responses (59).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies of prescapular lymph node samples from noninfected animals showed that the activity of MAb CC30 was not blocked by the respective MAbs used for CD4 ϩ cell depletion. Acetone-fixed cryosections of mandibular lymph nodes were labeled with IB11, a murine MAb shown to be specific for conformational, nonneutralizing epitopes of the FMDV capsid (35), in combination with CC51, dark-zone follicular dendritic cell marker D46 (anti-ovine fibrinogen, IgG2a) (39), and isotype-matched control MAbs TRT1, TRT3 (IgG2a) (17), and AV29. All MAbs used for confocal microscopy were produced at the IAH.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, moDC incubated with O1K-Cad2 IC induced significantly lower levels of proliferation, most likely as a result of CPE in the moDC. As FMDV does not infect bovine lymphocytes in vitro (data not shown) or in vivo (30), it is unlikely that the reduced CD4 ϩ T cell proliferative response was the result of a direct interaction with the virus.…”
Section: Vol 85 2011 Interaction Of Fmdv With Bovine DC 2215mentioning
confidence: 95%
“…In carrier cattle, virus replication has been detected within the pharyngeal epithelium, and it has been proposed that FMDV persists through sustained low-level replication (20,21). Virus particles have also been detected in lymphoid tissue germinal centers (GCs) in ruminants (22,23). Although virus replication has not been demonstrated, GCs have been proposed to be a virus reservoir with the potential for immune-complexed virus to infect lymphoid cells that migrate through GCs to the peripheral epithelium.…”
mentioning
confidence: 99%